Peran Media Animasi Untuk Meningkatkan Kemampuan Historical Imagination Siswa Dalam Pembelajaran Sejarah - Ali Wahyudi; Tarunasena Ma’mur (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
This research is entitled The Use of Animation Media to Enhance Students’ Historical Imagination Abilities in Learning History(Classroom Action Research in Grade X Social 3 Bandung 6 High School). That background is due to the low imagination of the historical students who are seen from the learning process of students who are less able to explore the material deeper. This research use the Classroom Action Research of Kemmis and McTaggart model. The model design consists of four stages namely plan, act, observation, and reflection. Based on the results of this study, by using the animation media students can be improved the historical imagination significantly after through three act for three cycles. As for the recommendations, it is expected that teachers, schools, and other researchers can take advantage of the use of this animation media to enhance the ability of Historical Imagination in learning history. Based on the results of research it can be explained that in the first cycle began to notice slight changes in student when action was first performed mainly on the historical imagination indicators but the time was interrupted by mid smester exam. The second cycle has more time, but unfortunately it has decreased because students seem bored with the action taken. In the third cycle increased again after the constraints experienced in previous cycle succesfully minimized in this action. The conclusion of animation media makes it easy for students to do re-enactment, interpolating, and interrogating about the presented material on each actions.